Context Comprehension of the Word in the Q uatrains of H.Tumanyan - BEKMEZYAN, ASTGHIK (Bulletin of Yerevan University B: Philology, 2021)
The problem of understanding the word as a literary unit, the literary meaning of the word in the context of a particular work is being examined in the article. Within the scope of the present study the quatrains of H. Tumanyan have been selected, where different connotations of every word – starting from the aesthetic and semantic context of each literary creation are obviously being distinguished.